The effects of vitamins and trace minerals on chronic autoimmune thyroiditis - Włochal, Małgorzata; Kucharski, Marcin A.; Grzymisławski, Marian (Journal of Medical Science, 2014)
Hashimoto’s thyroiditis (HT), also known as chronic lymphocytic thyroiditis is one of the most frequent types of inflammation of the thyroid gland. The prevalence of the overt HT is about 2% but it is believed that Hashimoto thyroiditis is more frequent than expected. Hashimoto’s thyroiditis is characterized by dysfunction of the immune system, which leads to impaired tolerance of own tissues and increased production of autoantibodies against the thyroid cells. Thyroid peroxidase antibodies (anti-TPO), thyroglobulin antibodies (anti-Tg) and/or TSH receptors antibodies are the principal markers of the disease. The essential element of the treatment of HT is the supplementation of L-thyroxine. In Hashimoto’s disease, like in many other autoimmune diseases, researchers attempted to support pharmacological treatment by adequate nutrition. The aim of this paper was to review the existing literature on the levels of antioxidants (vitamin A, C, E, selenium, zinc) and vitamin D in patients with HT, as well as the influence of the nutritional supplementation of the above mentioned elements on the metabolism of the thyroid gland hormones and the level of anti-thyroid peroxidase (anti-TPO) antibodies.